(untitled) (Research, Society and Development, 2022)
The aim of this study was to evaluate the effect of X radiation in single and fractionated doses in tibias of rats by micro-computer tomography (µCT) analysis. The sample was consisted by 20 male rats, divided into 3 groups: Control, Single dose and Fractionated dose. The rats were submitted to a radiation X exposure on lower limbs. The single dose group was exposed to single radiation of 15 gray (Gy), while the fractionated group was submitted to three irradiation sessions of 5 Gy each, totaling 15 Gy. After 24 hours and 25 days, the rats were euthanized; the tibias were removed and scanned using a µCT unit, SkyScan 1174 Compact Micro-CT (Kontich, Bélgica). The parameters total bone area (Tt.Ar) , cortical bone area (Ct.Ar) , total cross-sectional bone area ratio (Ct.Ar / Tt.Ar) e cortical thickness (Ct.Th) for cortical bone, e bone volume ratio (BV / TV), trabecular number (Tb.N), trabecular thickness (Tb.Th) e trabecular separation (Tb.Sp), for trabecular bone analysis were evaluated. Data were submitted to one-way ANOVA and Tukey’s test (α = 0.05). The µCT evaluation showed significant differences on Tt.Ar and Tb.Sp parameters (p<0,05). It was observed a lower Tt.Ar in the fractionated group compared to control, and higher Tb.Sp in the group receiving a single dose when compared to the control and fractionated groups. It is concluded, in relation to bone microarchitecture, that the radiation X in fractionated doses presents more deleterious effects on the cortical bone and when in singe doses, more damage on trabecular spaces, leading to a higher porosity.